The Anatel as a Republican Tool for the Internalization of International Rules - Oliveira, Artur Coimbra de (Law, State and Telecommunications Review, 2012)
The design and the actual implementation of regulatory authorities in Brazil played an important role in the historical tendency of displacing the legitimation center of public policies from the legislative to the executive branch, as the regulatory authorities’ law-making process became way more transparent and participative. Nevertheless, after the state reform movement that took place in Brazil during the 1990s, certain policies have not found their way to sufficient legitimation through the executive branch: international rules and soft law. This statement is supported by republican philosophy, which underlies modern state’s institutions, and by the concrete analysis of regulations in telecommunications services, as well as by observing the way the regulator deals with pertinent international administrative rules. This article concludes that this regulated area holds republican institutions that ensure universal political participation in the decision-making process, including the penetration of international law in the national environment. Nonetheless, in many cases these international standards and rules present themselves with an incoherent status and their internalizing processes often lack necessary steps in order to be in touch with a neo-republican conception of democracy.